CHARACTERISTICS OF JUWET FRUIT YOGHURT WITH THE ADDITION OF SKIM MILK AND LACTIC ACID BACTERIA STARTER - Wirdayat, Wira; Rosida, Rosida; Anugerah Dany P (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
In this study, the manufacture of juwet fruit yoghurt was studied with different treatments of adding skim milk and lactic acid bacteria starter. Yogurt is a processed milk product made through bacterial fermentation. Yogurt is known as a good source of protein, calcium, and probiotics, which can support digestive health and the immune system. Juwet fruit has a high antioxidant and vitamin C content so that juwet fruit has interesting potential to be made into yoghurt. Skim milk is used to utilize high lactose and protein so that the growth of lactic acid bacteria can grow optimally. Lactic acid bacteria are used for preservation, providing texture, and adding flavor to yoghurt drinks. The purpose of this study was to determine the addition of skim milk and lactic acid bacteria starter on the physicochemical, microbiological, and organoleptic characteristics of juwet yoghurt. This study used a Completely Randomized Design (CRD) factorial pattern consisting of two factors. Factor 1 addition of skim milk (5%, 7%, 9%). Factor 2 addition of starter (5%, 7%, 9%). Each treatment was repeated three times. The data obtained were analyzed using analysis of variance (ANOVA). If there is a significant difference between treatments, it is continued with the Duncan test (DMRT) and organoleptic test using the Scoring test with 25 trained panelists. The treatment of adding 9% skim milk and 9% starter was the best treatment that produced juwet yoghurt with a protein content of 2.1% ± 0.036, total titratable acid 2.1% ± 0.1, total soluble solids 22.7ºBrix ± 1.53, total lactic acid bacteria 10.5 log CFU/ml ± 0.023, pH 3.7 ± 0.058, antioxidants 34.0% ± 0.117, viscosity 6.8% ± 0.058, Vitamin C 5.8 ± 0.3, and organoleptic tests of color 2.88 (rather like), taste 3.24 (rather like), aroma 2.68 (rather like), texture 3.76 (like).